Girl who played with fire [videorecording (DVD)] = Flickan som lekte med elden - Alfredson, Daniel, 1959-; Rapace, Noomi, 1979-; Nyqvist, Michael, 1960-2017; Endre, Lena, 1955-; Larsson, Stieg, 1954-2004 (Music Box Films, 2010)
"In this second installment of Stieg Larsson's phenomenal 'Millennium' trilogy, Lisbeth Salander is a wanted woman. A researcher and a Millennium journalist about to expose the truth about the sex trade in Sweden are brutally murdered and Salander's prints are on the weapon. Her history of unpredictable and violent behavior makes her an official danger to society. Mikael Blomkvist, Salander's friend and Millennium's publisher, is alone in his belief of Salander's innocence. Digging deeper, Blomkvist unearths evidence implicating highly placed members of Swedish society--as well as shocking details about Salander's past. He is desperate to get to her before she is cornered--but no one can find her anywhere"--Container.